2004
DOI: 10.1136/jnnp.2002.003095
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of spontaneous recovery of neglect and associated disorders in acute right brain-damaged patients

Abstract: Objectives: The evolutionary pattern of spontaneous recovery from acute neglect was studied by assessing cognitive deficits and motor impairments. Detailed lesion reconstruction was also performed to correlate the presence of and recovery from neglect to neural substrates. Methods: A consecutive series of right brain-damaged (RBD) patients with and without neglect underwent weekly tests in the acute phase of the illness. The battery assessed neglect deficits, neglect-related deficits, and motor impairment. Age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
97
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 174 publications
(107 citation statements)
references
References 72 publications
(65 reference statements)
8
97
2
Order By: Relevance
“…The ANOVA conducted on cancellation tasks scores with the factor session showed similar results; the main effect of session was significant (F [2,18]ϭ13.52; PϽ0.0003; ϭ0.77). Post hoc tests showed that although an improvement was found between baseline (42%) and post-NP (57%; PϽ0.05) scores, the improvement was much stronger after PA (meanϭ77%; SDϭ18; PϽ0.008 for both comparisons).…”
Section: Additional Effect Of Prism Adaptation In Patients Undergoingmentioning
confidence: 59%
See 4 more Smart Citations
“…The ANOVA conducted on cancellation tasks scores with the factor session showed similar results; the main effect of session was significant (F [2,18]ϭ13.52; PϽ0.0003; ϭ0.77). Post hoc tests showed that although an improvement was found between baseline (42%) and post-NP (57%; PϽ0.05) scores, the improvement was much stronger after PA (meanϭ77%; SDϭ18; PϽ0.008 for both comparisons).…”
Section: Additional Effect Of Prism Adaptation In Patients Undergoingmentioning
confidence: 59%
“…Post hoc tests showed that although an improvement was found between baseline (42%) and post-NP (57%; PϽ0.05) scores, the improvement was much stronger after PA (meanϭ77%; SDϭ18; PϽ0.008 for both comparisons). Finally, the ANOVA conducted on reading accuracy scores showed a significant effect of session (F [2,18]ϭ7.58; PϽ0.005; ϭ0.60); reading accuracy was not significantly different before (77%) and after NP (81%; Pϭ0.09), whereas it was significantly higher after PA (meanϭ85%; SDϭ24; PϽ0.05 for both comparisons).…”
Section: Additional Effect Of Prism Adaptation In Patients Undergoingmentioning
confidence: 90%
See 3 more Smart Citations